Unbroken - Haas, Jessie (New York Greenwillow Books, 1999)
Following her mother's death in the early 1900s, thirteen-year-old Harry lives on Aunt Sarah's farm where an accident with her spirited colt leaves her a changed young woman
3
Keywords: Aunts -- Fiction; Death -- Fiction; Grief -- Fiction; Horses -- Fiction; Mothers and daughters -- Fiction; Orphans -- Fiction